PEMBANGKIT GETARAN FREKUENSI RENDAH MENGGUNAKAN SENSOR OPTOCOUPLER - Yoggy Refiyon (Department of Physics – Universitas Negeri Padang UNP, 2014)
Sensor is main component in measuring and controlling system. Somemany sensor using high technology in fabrication, like vibration sensor. It is making vibration sensor have high cost and rare. Because of that many researchers develop the vibration sensor, so that can ben get a sensor with low cost and good characteristic. To develop a vibration sensor with good characteristic needed a low frequency vibration generator as sensor calibrator. The goal of this research is knowing performance and design specification of low frequency vibration generator using optocoupler sensor. Kind of this research is laboratory experiment, and measurement technique and collecting data executed by directly and indirectly. Directly measurement is measuring output of sensor and time of count. Indirectly measurement is to determine accuration and precision of instrument. The data obtained through measurement analyzing in two methods, statics and graph. There are two result of this research, that are 1. Vibration generator that have two box casing( mechanical and electronic box), 2. Accuration of sensor is 94.4% with average of correctness 0.95477. Accuration average of vibration generator is 0.98 and the precision is 0.976. Keyword: vibration generator, low-frequency, seismic sensor, calibrator, optocopler counter